Posttranscriptional regulation of colonic epithelial repair by RNA binding protein IMP1/IGF2BP1. (7th July 2021) - Chatterji, Priya; Williams, Patrick A; Whelan, Kelly A; Samper, Fernando C; Andres, Sarah F; Simon, Lauren A; Parham, Louis R; Mizuno, Rei; Lundsmith, Emma T; Lee, David SM; Liang, Shun; Wijeratne, HR Sagara; et al.
Abstract :